A Study on the Factors Affecting the Adoption of IoT Systems in a DevOps-Enabled Environment - Mahawar, Bhawani Shankar (Digital Repository of Theses, 2024)
Purpose DevOps is, without a doubt, universally understood for its ability to accelerate delivery and enhance reliability in applications. Numerous stories of success in improving customer service have been pegged on the idea of DevOps. However, DevOps is still not widely adopted in the IoT field, where many components such as hardware, software and firmware are involved. The objective of this research is to explore the factors influencing the adoption of Internet of Things (IoT) systems within DevOps-enabled environments. The objective of this study is to identify and comprehend the various challenges and opportunities organizations face when integrating IoT technologies with their existing operational and development frameworks. Design /Methodology The study is based on original data collected from a targeted sample of 450 participants.. A conceptual framework incorporating UTAUT and the TTAT model been established. The study utilized purposive sampling for study, and data was collected through a carefully designed and a questionnaire that has been evaluated in advance. The study employed PLS-SEM analysis to evaluate the theoretical model. Findings The findings of the thesis indicate that the primary factor impacting the adoption of IoT systems in DevOps environments are perceived threat and effort expectancy. In contrast, the factors of perceived severity and perceived susceptibility yield a significant influence on the intention to use through perceived threat. Although there are other aspects like facilitating condition, performance expectancy, and social influence also play roles in adoption, their impact is relatively lower. Research Limitations Although this study has identified security as a critical component of perceived threat, there still exist potential limitations that future studies can address. More to the point, future research should further identify the complexities regarding the aspects of security characteristic of IoT systems. As such, novel frameworks should be developed to try and analyze new areas more fully and exhaustively. Moreover, regulatory measures should be taken accordingly, and the new approach to risk management characteristic of DevOps should be adapted to fit the various conditions set to difference the deployment of IoT. Therefore, addressing in more detail this approach, researchers will be able to make a more substantial contribution in terms of improving the security of system, as a result, streamlining the process of deployment of IoT within DevOps workflows. Originality Despite the existence of very few studies on IoT adoption or DevOps practices, none have explored the two topics together. This paper, therefore, combines the two domains into one paper, hence contributing to existing literature. In addition, using the Importance-Performance Map Analysis method and models such as the UTAUT and TTAT to analyze the adoption dynamics brings a new aspect to the existing literature. Therefore, based on the novel context, methodology, and analytical frameworks, the research can be seen as original and of good depth. Furthermore, the inclusion of case studies provides real-world examples to support the theoretical framework and considering the impact of leadership and social dynamics on IoT adoption, thus enhances the practical relevance and applicability of the research findings. The outcomes and findings can help future organizations adopt IoT in a DevOps-enabled environment.